Parameters Estimation of a Constrained Predator Prey Dynamical Model with Incomplete Data - Muzvondiwa, C.; Adeniji, A.A.; Fedotov, I.; Shatalov, M.Y.; Mkolesia, A.C. (Discontinuity, Nonlinearity, and Complexity, 2026)
Substantial frameworks for a predator prey dynamical model have been developed in the past. A Method for estimating parameters of a constrained dynamical model with incomplete data assuming information about predator (known) and prey (unknown) was investigated. Unknown parameters for the dynamical model was estimated using undetermined Lagrangian multiplier method. The method for estimating the parameters are based on the construction of a quadratic goal function minimization from a set of ordinary differential equations. A non-homogeneous system was generated using ordinary least square method applied to the goal function in order to estimate the parameters. The derivation of the parameters process was one of the inverse problem and the model with estimated parameters gave some satisfactory fit.